PENGARUH FIRM SIZE, LEVERAGE DAN ASSET MANAGEMENT TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN INFRASTRUKTUR (STUDI KASUS PADA PERUSAHAAN INFRASTRUKTUR TAHUN 2019-2023) - Luh Putu Puji Trisnawati (POLITEKNIK LP3I JAKARTA, 2025)
The infrastructure sector plays a strategic role in supporting economic development, making it essential to understand the internal factors influencing its profitability. This study aims to analyze the effect of firm size, leverage, and asset management on financial performance, as measured by Return on Assets (ROA) and Return on Equity (ROE), in infrastructure companies in Indonesia. The sample comprises 19 infrastructure companies listed on the Indonesia Stock Exchange (IDX), using secondary data from annual financial reports during 2019 – 2023. The analytical method employed is multiple linear regression using e-views software. The results show that firm size has no effect on ROA and ROE, leverage has a negative effect on ROA but no effect on ROE. Meanwhile, asset management has a positive effect on both ROA and ROE. These findings imply that infrastructure companies should prioritize efficient asset management and maintain a healthy capital structure to enhance profitability.